MRI-Based Identification of an Appropriate Point of Needle Insertion for Patients with Idiopathic Carpal Tunnel Syndrome to Avoid Median Nerve Injury. (6th July 2011) - Uchiyama, Shigeharu; Itsubo, Toshiro; Nakamura, Koichi; Murakami, Hironori; Momose, Toshimitsu; Kato, Hiroyuki
Abstract : To identify a safe entry point for needle insertion in patients with idiopathic carpal tunnel syndrome (CTS), cross-sectional images of the wrist MRI of 45 normal volunteers and 180 consecutive patients with idiopathic CTS were reviewed. Insertion of the needle from the five different entry points into the carpal tunnel was simulated by drawing a 1-pixel line, and the incidence of contact with the median nerve was compared. In the CTS patients, the lowest incidence was 3% when inserted at one-third of the length between the FCR and FCU tendons on the ulnar side at the level of the distal part of the distal radioulnar joint and 4% at the mid point between the palmaris longus tendona and the flexor carpi ulnaris tendon. It was greater in the advanced stage of CTS than the less severe CTS. We recommend those two entry points.